Parental emotionality and power relations in heritage language maintenance: experiences of Chinese and African immigrant families in Australia - Wang, Yining; Williams Tetteh, Vera; Dube, Sithembinkosi (Frontiers in Psychology, 2023)
Emotionality is increasingly given prominence in the field of language acquisition and socialisation in migration contexts. This cross-sectional study explores the emotional experiences of Chinese and African immigrant families in their practices of maintaining their children’s heritage languages. Data sources used to explore these experiences include transcriptions of open-ended interviews, fieldnotes from informal conversations and observations, photographic evidence of children’s literacy practices, and language portrait (LP) descriptions. An ethnographic analysis revealed a whole range of negative and positive parental emotions (e.g., anxiety, loss, and shame versus enjoyment, accomplishment, and pride), in the discourse of maintaining heritage and minority languages. The language emotions, whether positive or negative, are interpreted in-light of language ideologies, which specifically points to the significance of profit discourse in the formation of family language policies (FLPs). This materialistic valorisation reveals the complexities of power relations between English and minority languages, between Chinese and African languages, and within various Chinese/African languages. Consequently, the distinct hierarchies between English and minority languages and the hidden layers within minority languages further legitimate diasporic ideologies of Chinese and African parents in terms of prioritising, maintaining and forgoing languages. This study suggests that language emotionality is of vital importance to the psycho-social wellbeing of immigrant families and has practical implications for policy makers and heritage language research.